Weeding force saving to improve profitability of cassava-legumes cropping systems in eastern Democratic Republic of the Congo - Muke, A.; Nabahungu, N.L.; Kinche, K.; Vanlauwe, B.; Boeckx, P. (Elsevier, 2025)
Weeding is a common farming practice for optimal emergence, growth and maturity of crops. Smallholders in Central Africa use a traditional hoe for weed control. This is a hard and time-consuming activity. To address this bottleneck, a study was conducted at three sites, namely Walungu, Uvira, and Mulungu in South-Kivu in the Democratic Republic of the Congo (DRC), over two growing seasons (September 2020 and February 2021). The purpose was to minimize the workload involved in weed control and boosting cassava yields via time-, labour, and energy-saving through adjusted weeding. Experiments were carried out as a split-plot design with three randomized blocks at multiple locations. Weed control was assessed for hand hoe, herbicide, and single-wheeled hoe (a weeding tool that combines manpower with improved weeding precision) in a cassava-legume intercropping system. Results show that the use of herbicide translated into about 6 times less energy use than a hand hoe, accounting for a ca. 4 times reduced weeding workload, and a reduction in weeding time up to 84%. The single-wheeled hoe use accounted for almost 61% reduction in weeding energy consumed, a reduction of 40% of the weeding time, and for about 38% of the weeding load saving. Although the three weeding methods gave statistically similar yields, it nevertheless turned out that herbicide treatment achieved the lowest cost-benefit ratio (CBR) (0.2), evoking its superiority in terms of profitability over both the hand hoe and the single-wheeled hoe. The study asserted that weed control is ‘moderately heavy’ and ‘light’ when involving the single-wheeled hoe and herbicide, respectively.